Biochips nanotechnology - He, Nongyue; Nalwa, Hari Singh, 1954- (Stevenson Ranch, Calif. : American Scientific Publishers, 2009)
Nanotechnology has made it possible for a single chip to possess more than million features with supra-sensitive detection abilities than that of conventional methods. Nanotechnology has made biochips more applicable for commercialization purpose where biochips could be implanted inside body to dynamically transmit the information and monitor any biological changes in vivo. There has been significant progress on applications of biochips such as DNA chips, protein chips, and carbohydrate chips, and MEMS/NEMS in the field of medical nanotechnology. One could believe that when fused together, biochips and nanotechnology will endlessly bring scientists to newer and promising researching aspects. For this reason, this book on biochips nanotechnology was published. We also strongly believe that such a comprehensive book associated with various applications of nanotechnology in biochips will be helpful for people to develop new biochips devices, to find new application of nanotechnology and biochips in the coming years, and to bring out more commercialization of biochips and nanotechnology. Broadly speaking, this book covers all main aspects of biochip-based science and nanotechnologies.
Includes bibliographical references and index.
Keywords: Biochips; Nanotechnology; Oligonucleotide Array Sequence Analysis; Protein Array Analysis; Nanotechnology; Sequence Analysis, DNA -- methods